And then there was one: Polydora uncinata and Polydora hoplura (Annelida: Spionidae), the problematic polydorid pest species represent a single species. (13th July 2016) - Sato-Okoshi, Waka; Abe, Hirokazu; Nishitani, Goh; Simon, Carol A.
Abstract : It is necessary to monitor shell-associated polydorid worms owing to the risk that they pose to commercially important molluscs. This requires accurate identification, but is often hampered by morphological similarities among species, insufficient type specimens, and abridged species descriptions. Thus morphological characteristics and molecular sequences of the most harmful polydorid species, Polydora uncinata from Japan and Australia and Polydora hoplura from South Africa were compared to determine whether they represent two morphologically similar, but genetically distinct species, or a single species. A wide range of morphological variation (with respect to size, length of caruncle and pigmentation patterns) was observed in each species and population, and their variations largely overlapped and revealed them to be at the intraspecific level of a single species. This was confirmed by gene sequences of nuclear 18S and 28S rRNA that were completely identical for P. uncinata and P. hoplura . The mitochondrial 16S rRNA and cyt b gene analyses also showed no genetic differences between these two species. The tree topology of the mitochondrial cyt b gene did not reflect geographic differences but instead suggests artificial transportation of the species. We recommend the synonymization of P. uncinata with P. hoplura.